Pesan Nasionalisme dalam Youtube Bapak Erick Thohir - Maudhy Satyadharma; La Ode Rasidun; Muh. Arifin; Zulfikar Putera (Journal on Education, 2023)
The research seeks to analyze the content of nationalist messages on Mr. Erick Thohir's Official YouTube, especially regarding the U-17 World Cup Championship which will be held in Indonesia. This research was conducted using content analysis and is included in the qualitative category. The results of research using content analysis found that there were many nationalist messages in the form of sports reviews (sport nationalism), especially related to preparations for the U-17 World Cup and the enthusiasm of the Indonesian people for this championship which is closely related to nationalism